Effects of Selenium Supplement on B Lymphocyte Activity in Experimental Autoimmune Thyroiditis Rats. (11th August 2021) - Li, Yang; Zuo, Xinhe; Hua, Chuan; Zhao, Yong; Pei, Xun; Tian, Man
Abstract : Background and Objective . Thyroid is the organ with the highest selenium content in mammals, and selenium is an essential micronutrient that has close relationship with thyroid autoimmunity. However, the mechanism of how selenium modulates autoimmune thyroiditis remains to be elucidated. Thyroglobulin antibody (TGAb) and thyroid peroxidase antibody (TPOAb), which are produced by B lymphocytes, play a crucial role in autoimmune thyroiditis. The present study was aimed to investigate the effects of selenium supplement on thyroid autoimmunity and B lymphocyte activity in experimental autoimmune thyroiditis (EAT) model rats. Methods . 45 healthy and adult female SD rats were randomly divided into three groups: normal control group, EAT model group, and selenium yeast supplement EAT group. The EAT model rats were induced by subcutaneous injection of porcine thyroglobulin and fed with high iodine water. The concentrations of serum thyroid-stimulating hormone (TSH), TGAb, TPOAb, and B cell activating factor (BAFF) were detected in each group by enzyme-linked immunosorbent assay (ELISA), and the expression of interleukin-10 (IL-10) in thyroid tissue was detected by immunohistochemistry. B cells and regulatory B cells (Bregs) ratios in the spleen of rats were analyzed by flow cytometry. Results . In contrast with the EAT model group, the levels of serum TSH, TGAB, TPOAb, and BAFF were decreased, while IL-10 expression was increased in thyroid tissue, and Bregs ratio was upregulated in the spleen (all p < 0.05 ) in the selenium yeast supplement EAT group. Conclusion . Selenium yeast supplement could partially attenuate immune imbalance in EAT rats, which may be related to the mechanism of modulating B lymphocyte activity.